Prunella vulgaris L. Attenuates Experimental Autoimmune Thyroiditis by Inhibiting HMGB1/TLR9 Signaling - Guo Q (Dove Medical Press, 2021)
Qingling Guo,1,2 Haili Qu,3 Hong Zhang,4 Xia Zhong4 1Department of Endocrinology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, 250021, People’s Republic of China; 2Department of Endocrinology, Shandong Provincial Hospital, Cheeloo College of Medicine,Shandong University, Jinan, 250012, People’s Republic of China; 3Department of Nursing, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, 250021, People’s Republic of China; 4Department of General Practice, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, 250021, People’s Republic of ChinaCorrespondence: Xia ZhongDepartment of General Practice, Shandong Provincial Hospital Affiliated to Shandong First Medical University, No. 324 Jingwu Road, Huaiyin Distinct, Jinan, Shandong Province, 250021, People’s Republic of ChinaEmail zxbs1231@126.comBackground: Prunella vulgaris L. (PV) has been used to treat autoimmune thyroiditis (AIT), but the underlying mechanism remains unknown. The present study was designed to evaluate the effect of PV on AIT and explore the role of high-mobility group box-1 (HMGB1) signaling in PV-mediated effects in vivo and in vitro.Methods: In the present study, bioactive components of PV were identified using UPLC-ESI-MS. The protective effects and potential mechanisms critical for the anti-inflammatory and immunomodulatory effects of PV in AIT were investigated in a rat model of thyroglobulin-induced experimental autoimmune thyroiditis (EAT) and in lipopolysaccharide (LPS)-induced thyroid follicular cells (TFCs).Results: The main bioactive compound identified in PV was rosmarinic acid. The thyroid volume, thyroiditis inflammation score and serum thyroglobulin antibody levels of EAT rats were attenuated by PV treatment (P< 0.01). In addition, PV significantly reduced the elevated levels of the proinflammatory cytokines TNF-α, IL-6, IL-1β and monocyte chemoattractant protein-1 (MCP-1) both in vivo (P< 0.01) and in vitro (P< 0.05). PV downregulated HMGB1 mRNA and protein expression, reduced HMGB1 secretion, and inhibited TLR9 signaling pathways (TLR9 and MyD88) in PV-treated EAT rats and TFCs. Moreover, PV reversed the increases in the numbers of splenic Th1, Th2, and Th17 cells. Finally, our results acquired following administration of ethyl pyruvate, an HMGB1 inhibitor, to splenocytes cultured in vitro supported the hypothesis that the HMGB1/TLR9 pathway is involved in the PV-mediated reductions in Th1, Th2 and Th17 cells.Conclusion: PV decreased the activity of the TLR9/MyD88 pathway and proinflammatory cytokines through HMGB1. In addition, we are the first to show that PV attenuated the HMGB1-induced increases in Th1, Th2 and Th17 cells in AIT models. These findings provide new evidence for the potential therapeutic value of PV as a treatment for AIT and other autoimmune diseases.Keywords: autoimmune thyroiditis, Prunella vulgaris L., HMGB1, TLR9